2012
DOI: 10.1111/cpr.12002
|View full text |Cite
|
Sign up to set email alerts
|

Stability of human mesenchymal stem cells during in vitro culture: considerations for cell therapy

Abstract: Ex vivo expansion and manipulation of human mesenchymal stem cells are important approaches to immunoregulatory and regenerative cell therapies. Although these cells show great potential for use, issues relating to their overall nature emerge as problems in the field. The need for extensive cell quantity amplification in vitro to obtain sufficient cell numbers for use, poses a risk of accumulating genetic and epigenetic abnormalities that could lead to sporadic malignant cell transformation. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 46 publications
2
88
0
6
Order By: Relevance
“…Based on traditional karyotype analysis, some studies found that abnormal karyotype appeared in the culture of ADMSCs and BMMSCs. 10,11,37 However, whether MSCs with genomic anomalies gained the ability of forming tumor in vivo was unclear, even though chromosomal aberrations were found in cultured ADMSCs and BMMSCs. High-throughput methods were also used to investigate the genomic mutation of cultured ADMSCs and BMMSCs, 12,14 whereas, these studies failed to find significant genomic changes and stated that MSCs expanded in vitro confirmed an overall stability of genomic profile.…”
Section: Discussionmentioning
confidence: 99%
“…Based on traditional karyotype analysis, some studies found that abnormal karyotype appeared in the culture of ADMSCs and BMMSCs. 10,11,37 However, whether MSCs with genomic anomalies gained the ability of forming tumor in vivo was unclear, even though chromosomal aberrations were found in cultured ADMSCs and BMMSCs. High-throughput methods were also used to investigate the genomic mutation of cultured ADMSCs and BMMSCs, 12,14 whereas, these studies failed to find significant genomic changes and stated that MSCs expanded in vitro confirmed an overall stability of genomic profile.…”
Section: Discussionmentioning
confidence: 99%
“…Following isolation of the BM-MNCs using the Sepax method, a total of 10.82x10 9 BM-MNCs were collected from 8 donors. The absolute number of BM-MNCs per 1 mL of bone marrow after isolation was 4.1x10 6 ±7.8x10 5 .…”
Section: Collection Of Bone Marrow From 8 Healthy 3 Rd -Party Donors mentioning
confidence: 99%
“…The cells from each donor were re-suspended in cryomedium and frozen individually in bags. The total number of frozen BM-MNCs was 9.86x10 9 .…”
Section: Collection Of Bone Marrow From 8 Healthy 3 Rd -Party Donors mentioning
confidence: 99%
See 1 more Smart Citation
“…In a study using nine MSCs derived from bone marrow, a conventional cytogenetic analysis revealed random aneuploidies. In particular, one MSC presented with clonal trisomy 16 in p6 and p8 [31].…”
Section: Discussionmentioning
confidence: 99%